2007
DOI: 10.1515/hf.2007.064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical, mechanical and chemical properties of wood during sterilisation by gamma radiation

Abstract: Gamma irradiation, which is an easy, fast and effective method for wood sterilisation, changes molecular structures not only in pest cells, but also in wood cell walls. Radiation-induced depolymerisation causes significant changes in some properties of wood crucial for restoration and for laboratory testing of wood-preservative effectiveness, as demonstrated by experimental data. The influence of gamma radiation on maximum swelling (a MAX ), resistance to impact milling (RIM), and the total amount of water-sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Hasan (2006) and Despot et al (2007; found a strong influence of gamma irradiation on TSC. As gamma radiation causes destruction of cellulose chains and the resulting smaller cellulose fragments are easily soluble, increasing of TSC with increasing radiation dose was expected.…”
Section: Total Amount Of Water-soluble Carbohydrates (Tsc)mentioning
confidence: 97%
See 4 more Smart Citations
“…Hasan (2006) and Despot et al (2007; found a strong influence of gamma irradiation on TSC. As gamma radiation causes destruction of cellulose chains and the resulting smaller cellulose fragments are easily soluble, increasing of TSC with increasing radiation dose was expected.…”
Section: Total Amount Of Water-soluble Carbohydrates (Tsc)mentioning
confidence: 97%
“…Hasan (2006) and Despot et al (2007; measured the total amount of water-soluble carbohydrates (TSC) according to Rapp et al (2003). They used the following procedure: Five oven-dried specimens of each group were milled together for 60 s in a heavy vibratory disc mill (Herzog Maschinenfabrik, Osnabrück, Germany).…”
Section: Total Amount Of Water-soluble Carbohydrates (Tsc)mentioning
confidence: 99%
See 3 more Smart Citations